Association between out-of-pocket health expenditure and the disease burden of diabetes mellitus: insights from GBD 2021 - Luyou Dong; Zhifu Dong (Frontiers in Public Health)
ObjectivesAs one of the most common chronic diseases, diabetes mellitus poses a significant challenge to healthcare systems. This study analyzes the relationship between out-of-pocket (OOP) expenditure levels and the disease burden of diabetes mellitus, provides evidence-based recommendations for optimizing OOP expenditure strategies, and seeks to uncover any potential impact of healthcare inequalities on the disease burden of diabetes mellitus.MethodsThis cross-sectional study was performed among 36 countries with varying percentages of OOP payments from Health System in Transition. Data on Disability-Adjusted Life Years (DALYs), obesity rates, OOP expenditure as a percentage of current health expenditure (CHE), and urbanization levels were sourced from the Global Burden of Disease (GBD) database, World Health Organization, and World Bank. Statistical analyses in RStudio included the Welch's two-sample t-test and multiple linear regression.ResultsHigh OOP expenditure countries exhibited significantly higher diabetes-related DALYs (M = 965.98) versus low OOP groups (M = 556.33, 95% CI [103.99–715.32], p = 0.01). Regression analysis identified that low OOP expenditure, higher obesity rates, and greater urbanization levels were significantly associated with diabetes-related DALYs (β = −419.67, β = 37.31, and β = 8.07, respectively; all p < 0.05), explaining 51% of the variance (R2 = 0.51) with no evidence of multicollinearity (VIF <2).ConclusionsThis study shows that countries with high OOP expenditure tend to experience a significantly greater disease burden of diabetes mellitus, with obesity and urbanization levels being important correlates of diabetes-related DALYs.